PAPAYA LEAFE EXTRACT FOR REGENERATION OF PLATELET IN BLOOD - T Gutter, Vance; Shiri, Himashi (International Journal of Multidisciplinary Research and Studies, 2021)
Papaya (Carica papaya Linn) is well known for its exceptional nutritive and medicinal parcels throughout the world. From ancient times, the Papaya and its components such as leaves, seeds, and roots are being used for medicinal purposes. This delicious fruit of Papaya is popular among family members of all periods for the succulent dishes deduced from it. There are various which you can even say a lot of benefits of papaya are owed due to the high content of Vitamins A, B, and C, proteolytic enzymes such as papain and chymopapain which have antiviral, antifungal, and antibacterial parcels. Carica papaya can be used for the treatment of multitudinous conditions like knobs, sludge, sinuses, eczema, cutaneous outgrowths, glandular excrescences, blood pressure, dyspepsia, constipation, amenorrhoea, general fragility, expel worms, and vitalizing reproductive organs apart from these there are much more benefits as a result, Carica papaya can be regarded as a Neutraceutical. In the present review composition, a humble attempt is made to show how this fruit is useful in the regeneration of blood platelets. This delicious fruit is for all age groups.